An academic achievements visualization research in the past 30 years: research on rehabilitation for head and neck cancer - Zhou, Bo; Li, Dian; Cheng, Jingyi; Deng, Kexin (Frontiers in Oncology, 2024)
Background Head and neck cancer acts as the sixth most common malignant tumor worldwide with an increasing incidence. The needs and methods of its rehabilitation are diverse and constantly evolving. Objective This study aims to provide an in-depth depiction and visualization of the knowledge structure, hotspots, and emerging trends within the domain in the past 30 years through utilizing bibliometric analysis. Methods The literature about rehabilitation for head and neck cancer in Web of Science was collected. CiteSpace and VOSviewer were used to analyze main countries, institutions, authors, journals, subject hotspots, trends, frontiers, etc. Results A total of 1869 papers have been published since 1994. These publications were written by 874 authors from 514 institutions in 74 countries. The United States published 397 papers in this field and ranked first. Head & Neck is the most widely published journal, with Finizia, Caterina as the core author. The main keyword clustering includes terms such as #0 mandibular reconstruction (2009); #1 functional impairment (2014); #2 device lifetime (2006); #3 head and neck cancer (2003); #4 maxillofacial prosthetics (2004); #5 squamous cell carcinoma (2002); #6 readiness for return to work (2009); #7 total laryngopharyngectomy (2004). The current research frontier that has been sustained is “survivors”, “reliability”, and “meta analysis”. Conclusion We reveal the current status, hotspots, and trends in the field of rehabilitation for head and neck cancer. And we provided new academic insights into the characteristics and limitations of the field’s development.